Annexin and Survivin in locally advanced rectal cancer: indicators of resistance to preoperative chemoradiotherapy? - Horisberger, Karoline; Erben, Philipp; Ströbel, Philipp; Bohn, Beatrice; Hahn, Melanie Inés Fee; Kähler, Georg; Wenz, Frederik; Hochhaus, Andreas; Post, Stefan; Willeke, Frank; Hofheinz, Ralf-Dieter (Onkologie, 2010)
Background: The aim of preoperative chemoradiotherapy is improvement of local control in patients with locally advanced rectal cancer (LARC). Recent studies have shown that annexin and survivin are involved in the resistance capability of tumours. We sought to determine whether survivin, annexin A4 or annexin A5 expression predict resistance to preoperative chemoradiotherapy. Material and Methods: Biopsies of tumour and normal rectal tissue were taken from 38 patients with LARC (cT3/4Nx or Tx/N+) before the start of chemoradiotherapy and during surgery. mRNA expression of annexin A4/A5 and survivin was measured by real-time polymerase chain reaction (RT-PCR) and correlated with down-staging and progression-free survival (PFS). Results: Significantly higher mRNA levels of survivin, and annexin A4/A5 were detected in untreated tumour compared with normal mucosa. After chemoradiotherapy, this difference disappeared for survivin and annexin A4. Annexin A5 expression in the tumour increased during chemoradiotherapy. No correlation between the mRNA levels of survivin, annexin A4/A5 and tumour down-staging or PFS was noticed. Conclusions: In the present analysis of 38 patients with LARC undergoing neoadjuvant chemoradiotherapy, the expression levels of survivin and annexin A4 and A5 did not correlate with down-staging. Moreover, with regard to PFS, none of these markers was found to be prognostically relevant.